Peranan Laser Derajat dalam Pengembangan Pembelajaran Pendidikan Matematika Realistik - Robin Tarigan (Sepren, 2022)
Mathematics is one of the subjects taught in school. The process of converting mathematical abstraction into concrete requires Realistic Mathematics Education Learning. In the Development of Realistic Mathematics Education requires learning media. The Learning Media is Laser Degrees for learning Trigonometry in the Elevation Angle sub-subject. The purpose of this study is the relationship between students' competence in using Laser Degrees in measuring the height of objects with the results of calculating the height of objects measured using Laser Degrees. The sample is 52 people with research results with rank correlation that the calculation of the value of r' is equal to 0.982. Based on this value, it is obtained that Z count (Zh) is equal to 7.0184. For = 5%, Z table (Zt) is equal to 1.96. Because Zh is greater than Zt, it is concluded that Reject Ho or accept Ha, that is, there is a significant relationship between X and Y variables. The decision is that there is a relationship between students' competence in using Laser Degrees in measuring the height of objects with the results of calculating the height of objects measured using Laser Degrees.